Identification and characterization of six new mutations in GLB1 gene in Ukrainian patients with GM1 gangliosidosis and Morquio B disease - Mytsyk, N.Y.; Gorovenko, N.G. (Вiopolymers and Cell, 2016)
GM1-gangliosidosis (MIM# 230500) and mucopolysaccharidosis IV (Morquio B, MIM# 230500) are autosomal-recessive diseases, which belong to the group of lysosomal storage disorders and are caused by changes in the structure of the same gene, GLB1. The mutations in GLB1 lead to deficiency in acid β-galactosidase, and, as a result, the accumulation of GM1-gangliosidosis and keratan sulphate in the patients’ lysosomes. Aim. To analyze the spectrum of mutations in GLB1 in Ukrainian patients with GM1 gangliosidosis and Morquio B disease. Results. We analyzed GLB1 in 25 Ukrainian patients with the diagnosis of GM1-gangliosidosis and one patient with Morquio B disease; 52 alleles were analyzed. Seventeen types of pathogenic mutations were identified, including 11 missense replacements, three deletions, one insertion and two mutations in the splicing site. The missense mutation p.His281Tyr (c.841C>T) in exon 8 was found to be the most common, as it was found in 19 out of 52 mutant alleles (36.5 %) of all the examined patients. The study allowed to identify six new mutations, which had not been found in any databases or previously described in scientific literature, including three deletions (c.699delG, c.833delG, c.1203_1205delTTA), two missense replacements (p.Gly243Arg, p.Gly262Ala) and one mutation in the splicing site (IVS12+8T>C). Conclusions. Our results can be used for a precise molecular diagnostics of patients with GM1-gangliosidosis and Morquio B disease and prenatal diagnostics in the high risk families.